(untitled) (Malaysian Management Journal, 1999)
Book Review Title Pencukaian Malaysia - Pentad biran, Penaksiran dan Pematuhan Cukai Author Jeyapalan Kasipillai & Mustafa Mohd. Hanefah Universiti Putra Malaysia Press Total Pages 249 ISBN 983-9319-40-X Reviewer Ho Juan Keng Faculty of accounting Universiti Teknologi Mara (UiTM), Malaysia